The Improvement of Science Teachers’ Competence in Developing the Integrated Sciences Worksheets Based on Scientific Literacy to Support the Implementation of the Merdeka Curriculum - Wahyuni Satria Dewi; Mairizwan Mairizwan; Renol Afrizon; Khairil Arif; Putri Dwi Sundari (Postgraduate, University of Mataram, 2022)
In preparation for the implementation of the Merdeka Curriculum, science learning in schools still has problems, namely; 75% of science teachers have not been able to design real problems in everyday life as scientific contexts, and only 50% of science teachers can integrate science material in an integrated manner on worksheets, and there are still very few science teachers who are ready to implement the curriculum. The purpose of this study was to determine the effect of providing technical guidance (Bimtek) on developing scientific literacy-based worksheets on the competence of science teachers. The Bimtek activity consists of six stages: pretest, material debriefing, technical guidance (Bimtek), independent activities, evaluation monitoring, and posttest. From the Bimtek activities carried out for science teachers at MGMP Pesisir Selatan districts significantly increased teacher competence in developing scientific literacy-oriented worksheets. Based on the results of data analysis and discussion, it was found that the post-test average score was higher than the pretest average score. The science teacher pretest average score was 39.95, while the science teacher posttest average score was 62.10. The percentage increase in teacher competence is 23%.